Sheikh Al-Khaleesi in the book “Faisal I, King of Iraq” - Kani, Ass.Prof Dr Maha Mazhar (Thi Qar Arts Journal, 2023)
Criticism of historical books is known for its positive and negative critical evaluation of their historical content. It involves analyzing the strengths and weaknesses of the book and assessing its historical scholarly quality. In this historical scientific study, we attempted to provide implicit detailed analytical criticism and evaluate the historical text of the book "Faisal I, King of Iraq." We focused on studying, analyzing, and drawing conclusions from the religious authority of the Khaleeji lineage in the city of Kazimiyah and its religious and political impact on modern Iraqi history. Throughout this study, we presented the reader with a brief introduction to the basic information about the book and its author. We analyzed the historical content of the book by rephrasing the author's conclusions and providing comments supported by documents on each conclusion related to the topic of the Khaleeji family leaders, Sheikh Mahdi and his son Sheikh Muhammad Al-Khaleesi. We also considered the author's writing style and evaluated the organization of the book presented for study and its use of references and other methodological aspects¹.Contemporary Iraqi history holds significant importance in scientific studies across its political, historical, and social aspects. Recognizing the historical memory of this intellectual heritage and invoking it for successive generations through a rigorous scientific approach is crucial. Our study specifically analyzed the positions of the Khaleeji religious authority in the book "Faisal I, King of Iraq," which comprehensively documents the life of one of the most significant rulers in Iraq's entire history. Faisal I stands out as a prominent figure in the Middle East during a sensitive historical period. His role was pivotal in establishing modern Iraq in 1921. As nations take pride in their national heroes, fighters, and martyrs, the Iraqi memory should always honor the life milestones of Ayatollah Sheikh Muhammad Mahdi Al-Khaleesi (1860-1925), who was a national hero and a fighter. He also served as the highest religious authority during the reign of King Faisal I¹.